THE INFLUENCE OF THE MOTIVE FOR USING INSTAGRAM SOCIAL MEDIA AND THE QUALITY OF INFORMATION ON THE @LAMPUNGKULINER ACCOUNT ON FOLLOWERS SATISFACTION IN CHOOSING A PLACE TO EAT IN BANDAR LAMPUNG CITY - Ati, Henny Dewi Laras; Viranisa, Salsabilla Ninday; Sentana, Geo Citra (Universitas Sang Bumi Ruwa Jurai, 2023)
This research aims to analyze the influence of motives for using Instagram social media and the quality of information on the @LampungKuliner account on followers' satisfaction in choosing a place to eat in Bandar Lampung City. This research uses a survey method and data collection is carried out through questionnaires given to followers of the @LampungKuliner account. The results of the analysis show that the motive for using Instagram social media has a significant effect on followers' satisfaction in choosing a place to eat in Bandar Lampung City. Entertainment motives and information motives are the main factors that influence follower satisfaction. Followers who use Instagram with an entertainment motive are more likely to feel satisfied when choosing a place to eat, because the @LampungKuliner account provides interesting and entertaining content. Apart from that, followers who use Instagram with an information motive are also more likely to feel satisfied, because the @LampungKuliner account provides quality information about places to eat in Bandar Lampung City. Apart from that, the quality of the @LampungKuliner account information also has a significant influence on followers' satisfaction in choosing a place to eat. Followers consider that this account provides accurate, relevant and reliable information about places to eat in Bandar Lampung City. This gives followers confidence in making decisions about where to eat, thereby increasing their satisfaction. This research provides an important contribution to understanding the influence of motives for using Instagram social media and the quality of information on the @LampungKuliner account on followers' satisfaction in choosing a place to eat in Bandar Lampung City. The results of this research can be a reference for culinary social media account owners to improve the quality of the content and information presented, so that it can influence followers' satisfaction in choosing a place to eat.